Challenges of land services delivery and effectiveness of emutation in Bangladesh: a study on land mutation at Maheshpur upazila Jhenaidah - Akther, Rozina (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2020.